USING CELLULOSE GUM TO IMPROVE THE PHYSICOCHEMICAL, RHEOLOGICAL, AND SENSORY PROPERTIES OF LOW-FAT MOZZARELLA CHEESE - Shaymaa Saady Lafta (The Iraqi Journal of Agricultural science)
This study was aimed  to investigate the potential of cellulose gum as a substitute for fat in Mozzarella cheese production and evaluate its impact on the cheese's physicochemical, rheological, and sensory properties. Cellulose gum was added in different ratios of 0.1, 0.2, 0.3, 0.4, and 0.5%, revealing treatments  A1, A2, A3, A4, and A5 to skimmed milk, respectively. As well as the positive control treatment C+ manufactured from whole milk, there is a negative control treatment C- made from skimmed milk without cellulose gum. After processing, several tests were conducted to determine the quality of the product. Chemical tests were carried out to measure moisture, protein, fat, lactose, and ash  and total acidity  percentage. Physical tests were also conducted, including, pH, compression, and elasticity measurements. In addition, sensory evaluations were conducted immediately and after 120 days of storage at (5 ± 1) º C. The results revealed that the cellulose gum treatments contained a higher moisture content than C+ and C- recorded at 48.13 and 50.40 %, respectively. In comparison, it varied from 56.85 to 55.00 % for cellulose gum treatments A2 (the best treatment in sensory properties). During 120 days of storage at (5±1)ºC, all treatment values significantly reduced moisture content. Fat content increased significantly in all cellulose gum-treated skimmed milk, while lactose percentage remained constant across all treatments. Adding cellulose gum to cheese production improved its rheological test results for compression and elasticity compared to the control group. Also, adding cellulose gum enhanced cheese yield and improved the sensory properties of low-fat Mozzarella cheese.